Research and Implementation of Quality Management System for ERP System - Shuo Shan; Guanxun Guo; Jing Mai (Dianxin kexue)
The applications and business of CGN ERP system is in-depth expansion.The critical path and advantages of ITIL,ISO20000,CMMI and other standard system were analyzed.CGN ERP quality management system was implemented.It runs ERP systems as the thinking of running power station.The nuclear safety culture was blended into the quality level and process control of system.Through the successful implementation of quality management system,to protect the ERP system is in safe and stable operation,to ensure the core business processes are in the continuation and development,to bring the information values to the users.